2019
DOI: 10.1186/s12875-019-1028-2
|View full text |Cite
|
Sign up to set email alerts
|

Why do general practitioners not refer patients to behaviour-change programmes after preventive health checks? A mixed-method study

Abstract: Background This study was embedded in the Check-In randomised controlled trial that investigated the effectiveness of general practice-based preventive health checks on adverse health behaviour and early detection of non-communicable diseases offered to individuals with low socioeconomic positions. Despite successful recruitment of patients, the intervention had no effect. One reason for the lack of effectiveness could be low rates of referral to behaviour-change programmes in the municipality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Implementation of screening and brief intervention protocols for alcohol problems have been a challenge in primary care for the past decades [ 23 , 24 ], and so has bridging the gap between primary care and specialized treatment options [ 49 , 50 ]. The 15-method includes aspects which can improve implementation of behavioral change interventions, such as training and education [ 51 55 ], on-the-job experience with the intervention [ 54 ] and the possibility of interdisciplinary approaches [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of screening and brief intervention protocols for alcohol problems have been a challenge in primary care for the past decades [ 23 , 24 ], and so has bridging the gap between primary care and specialized treatment options [ 49 , 50 ]. The 15-method includes aspects which can improve implementation of behavioral change interventions, such as training and education [ 51 55 ], on-the-job experience with the intervention [ 54 ] and the possibility of interdisciplinary approaches [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient recruitment has previously been described as a ‘sales pitch’ [ 35 , 39 ], which poses a major challenge to healthcare providers. Furthermore, research shows that healthcare providers do not feel comfortable communicating the aims and design of the trial, do not want their patients to feel pressured to participate, and do not feel comfortable dealing with rejection [ 35 , 39 , 40 ]. Offering recruitment skills training in trial preparation workshops can overcome these barriers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual content of these extra consultations is unknown. A recent Danish study evaluating the effect of preventive health checks in high-risk groups found that only a low proportion of high-risk participants was visiting their general practitioner following a health check, 24 and that general practitioners had several barriers towards referral to municipal behaviour change programmes. 24 Third, although performed in a real-world setting, the CHPP was designed as a health promotion intervention with focus on the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Danish study evaluating the effect of preventive health checks in high-risk groups found that only a low proportion of high-risk participants was visiting their general practitioner following a health check, 24 and that general practitioners had several barriers towards referral to municipal behaviour change programmes. 24 Third, although performed in a real-world setting, the CHPP was designed as a health promotion intervention with focus on the individual level. Indeed, the CHPP had local media coverage; however, there were no formalised efforts to decrease disease risk at the local structural level or by explicitly targeting interindividual social connections.…”
Section: Discussionmentioning
confidence: 99%